The Least Developed Countries Report 2021 - United Nations Conference on Trade; Development (United Nations, 2021)
This publication takes stock of 50 years of development experience since the establishment of the LDC category in 1971. Most LDCs growth has been erratic, and they have not closed the income gap with other developing countries. This stems largely from the inefficacy of domestic and international policies in addressing structural impediments to structural transformation, i.e. low level of productive capacities, excessive export orientation, limited policy space, weak state capacity, technological backwardness, limited entrepreneurial development and insufficient investment in human capital formation. For the coming decade, the report proposes an overhaul of development policies and strategies in favour of initiatives that are centred on the development of productive capacities and led by a developmental state, which successfully aligns foreign agents’ dealings with LDCs to national development goals and priorities.